THE USE OF VISUAL ART TO FACILITATE STUDENTS IN LEARNING ENGLISH SPEAKING AT SMK NEGERI 2 MAKASSAR - St. Rahma Wahyuni Amirullah; Nurdevi Bte Abdul; Hilda Hafid (English Language Teaching Methodology, 2022)
This thesis aimed to find out does the use of Visual Art media improve the students to speaking accuracy and make the students in easier at in speaking fluency at SMK Negeri 2 Makassar. The researcher applied pre-experimental method with one gruoup pre-test and post-test design. To collect the data, the researcher used pre-test, treatment and post-test. The result of this research showed that the result of t-test value of level significant (p) = 0.05 with degree of freedom in accuracy (pronunciation) (df) + 29. In fluency (smoothness) (df) + 29. Indicated t-table value is 1.6991 and t-table accuracu (pronunciation) is 16.784, in fluency (smoothness) 14.262. Based on the result data analysis, it is concluded that there is difference significant mean score of the test that have given by researcher using Visual Art media in teaching speaking.